Early Transcriptional Responses After Dengue Vaccination Mirror the Response to Natural Infection and Predict Neutralizing Antibody Titers. (14th July 2018) - Popper, Stephen J; Strouts, Fiona R; Lindow, Janet C; Cheng, Henry K; Montoya, Magelda; Balmaseda, Angel; Durbin, Anna P; Whitehead, Stephen S; Harris, Eva; Kirkpatrick, Beth D; Relman, David A
Abstract : Interferon- and cell cycle–associated gene transcript abundance levels in the peripheral blood of dengue vaccine recipients on days 8 and 9 postvaccination were associated with dengue neutralizing antibody titers on day 42, and mirrored responses in primary dengue infection, suggesting the possibility of predicting protective immunity. Abstract: Background: Several promising live attenuated dengue vaccines are in development, but information about innate immune responses and early correlates of protection is lacking. Methods: We characterized human genome-wide transcripts in whole blood from 10 volunteers at 11 time points after immunization with the dengue virus type 3 (DENV-3) component of the National Institutes of Health dengue vaccine candidate TV003 and from 30 hospitalized children with acute primary DENV-3 infection. We compared day-specific gene expression patterns with subsequent neutralizing antibody (NAb) titers. Results: The transcriptional response to vaccination was largely confined to days 5–20 and was dominated by an interferon-associated signature and a cell cycle signature that peaked on days 8 and 14, respectively. Changes in transcript abundance were much greater in magnitude and scope in symptomatic natural infection than following vaccination (maximum fold-change >200 vs 21 postvaccination; 3210 vs 286 transcripts with significant fold-change), but shared gene modules were induced in the same sequence. The abundances of 131 transcripts on days 8 and 9 postvaccination were strongly correlated with NAb titers measured 6 weeks postvaccination. Conclusions: Live attenuated dengue vaccination elicits early transcriptional responses that mirror those found in symptomatic natural infection and provide candidate early markers of protection against DENV infection. Clinical Trials Registration: NCT00831012.